The complete chloroplast genome sequence of Artocarpus hypargyreus. Issue 1 (2nd January 2020) - Li, Dong-Lin; Gul, Juma; He, Jin-Ming
Abstract: The complete chloroplast genome sequences of Artocarpus hypargyreus was reported in this study. The length of the sequence was 160, 952 bp in length with a large single copy (LSC) region of 89, 476 bp, the small single copy (SSC) region of 20, 070 bp and two inverted repeat (IR) regions of 25, 703 bp. The complete genome contains 129 genes including 84 protein-coding genes, 8 rRNA genes and 37 tRNA genes. Phylogenetic analysis of the Moraceae based on 8 plastome sequence shows that A. hypargyreus is most related to Morus cathayana .